Dengue therapeutics, chemoprophylaxis, and allied tools: state of the art and future directions. - James Whitehorn; Sophie Yacoub; Katherine L Anders; Louis R Macareo; M Cristina Cassetti; Vinh Chau Nguyen Van; Pei-Yong Shi; Bridget Wills; Cameron P Simmons (PLoS Neglected Tropical Diseases)
Dengue is the most common arboviral disease of humans. There is an unmet need for a therapeutic intervention that reduces the duration and severity of dengue symptoms and diminishes the likelihood of severe complications. To this end, there are active discovery efforts in industry and academia to develop interventions, with a focus on small molecule inhibitors of dengue virus replication that are suitable for therapy or chemoprophylaxis. Advancements in animal models of dengue virus infection together with the possibility of a dengue human infection model have further enhanced the platform for dengue drug discovery. Whilst drug discovery efforts gestate, there are ongoing clinical research designed to benefit today's patients, including trials of supportive care interventions, and descriptive studies that should improve the ability of clinicians to make an accurate diagnosis early in the illness course and to identify patients most at risk of progression to severe disease. This review provides a state of the art summary of dengue drug discovery, clinical trials, and supportive allied research and reflects discussions at the 2nd International Dengue Therapeutics Workshop held in Ho Chi Minh City, Vietnam, in December 2013.